Effect of some non-genetic factors on birth weight and pre-weaning growth pattern in Kedah-Kelantan Calves - Intan Sofienaz Ahmad Fuad; Md. Ruhul Amin; Nor Dini Rusli (Universiti Malaysia Kelantan, 2014)
Birth weight records of 738 Kedah Kelantan (KK) calves and 30 records on their 3 and 6 months body weight were obtained from Pusat Ternakan Haiwan Pantai Timur (PTHPT), Tanah Merah, Kelantan during the period of 2010- 2012. Data for this study were collected to identify non-genetic factors that affect birth weight and to observe growth performance of KK calves. The nongenetic factors that encompassed in this study were sex of calves, year of birth, season of birth and parity of dam. Growth performance was divided into two periods which were ADG 1 (Average Daily Gain) (birth to 3 month) and ADG 2 (3 to 6 month).The study revealed that effect of sex of calves and year of birth were highly significant (p<0.01) on birth weight of KK calves. Birth weight of male and female calves averaged at 14.27 kg and 13.50±0.058 kg respectively. Effect of season of birth and parity of dam were insignificant (p>0.05) on birth weight of KK calves. Growth performance of KK calves was found to be 338.148±15.565 g/day and 247.407±45.254 g/day for ADG 1 (birth to 3 month) and ADG 2 (3 to 6 month) respectively. Little but significant improvement in birth weight of calves over the years might be partly due to genetic selection of breeding bulls.